Ø§Ù„Ø¬Ù…Ù„Ø© ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© (Ø¯Ø±Ø§Ø³Ø© ØªÙ‚Ø§Ø¨Ù„ÙŠØ© Ø¨ÙŠÙ† Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù†ØÙˆ Ø§Ù„ØªÙ‚Ù„ÙŠØ¯ÙŠØ© ÙˆØ§Ù„ØØ¯ÙŠØ«Ø©) - Roviin, Roviin (IAIN Salatiga, 2017)
This article discusses about the difference between traditional and modern nahwu schools in studying of the Jumla (sentence). Jumla is a compound words because it is a combination of two or more words. Traditional nahwu schools agree that the jumla is any structure that fully benefits. The modern nahwu schools hold that the jumlaÂ is all statements consisting of two principal things, the first is the earlier one and the second is the last part which has the function of statement or question and the other. The traditional nahwu schools divide the jumlaÂ into two parts, the first is the ismiya and the second is fi'liya. The jumla ismiya consists of mubtada and khobar while the jumla fi'liya is composed of fi'il and fa'il. The division of jumla according to modern nahwu schools is the jumla basitho and the jumla murokkaba. TheÂ jumla basitho consists of one composition only, while the jumla murokkaba consists of musnad and musnad ilaih. TheÂ jumla ismiya can be defined as a musnad in which the form of words, phrases or compositions. Whereas if the musnad is a fi'il structure then it is called the composition of fi'liyah, either consisting of words, phrases or compositions.